A randomised controlled trial of the effect of the provision of free school milk on the growth of children. Issue 1 (March 1980) - Baker, I A; Elwood, P C; Hughes, J; Jones, M; Moore, F; Sweetnam, P M
Abstract : A randomised controlled study was carried out of the effect on growth of the provision of free milk supplements to schoolchildren aged 7 and 8. In selecting children for this study, the aim was to identify those whose socioeconomic circumstances might place them at a disadvantage for growth. Five hundred and eighty-one-children were selected from schools where a high proportion of the pupils received free school meals, and from families with four or more children. The subjects were randomly allocated to receive a third of a pint (190 ml) of free milk daily for six school terms or to a control group. The mean difference in height gain at the end of twenty-one-and-a-half months was 3% or 2.93 mm (P less than 0.05) in favour of the children provided with free milk. The mean difference in weight gain was 130 g (P greater than 0.05) in their favour. The height and weight gain associated with the provision of free mild was very small in the study population, and it is therefore likely that the benefit to growth of providing free milk for the whole unselected population of schoolchildren of these ages would be even smaller.